Strategic management in education: concept, practice, and impact on the quality of education - Rahma, Anita (Professorline, 2024)
This paper explores the concepts, practices, and implications of strategic management in education. Strategic management is the ability to set an educational organization's vision, mission, goals, and strategies that meet the needs and challenges of the future. Strategic management also includes the skills to manage resources, collaborate, and create a conducive learning culture. This article outlines several models and theories of strategic management and examples of strategic management practices in several countries. This article also deals with the impact of strategic management on the quality of education, both in terms of the learning process, student learning outcomes, and the effectiveness of educational organizations. This paper argues that strategic management is an essential factor that can improve the quality of education in an era of globalization and rapid change.